ILRI 40 years panel discussion on livestock and sustainable food and nutritional security - International Livestock Research Institute (International Livestock Research Institute, 2014)
Panel discussion moderated by Joyce Cacho at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives. ILRI@40 conference, Addis Ababa, Ethiopia, 6–7 November 2014.